Table of Content - -, (Journal of Islamic Sciences, 2023)
Table of Content:1. Supply contracts, A comparative jurisprudential studyMrs. Abrar Rizq Allah Alsulami2. The disagreement reasons about belief in predestination between Ahl Al-Sunnah Wa’l-Jama’ah  and those who oppose them (review&  study)Mr. Saad Ibrahim Abdullah Al Ahmed3. Ibn Al-Zaghuni’s approach to his jurisprudential choices - prostration of forgetfulness  and voluntary prayer chapter as a sampleMrs. Abeer Farhan Hasan, Prof. Hussain Mualwi Al-Shahrani4. Analytical study of Al-Hawi's book, by Imam Abi Al-Hassan Ali bin Mohammed Al-Basri, Al-Mawardi Al-Shafei, 450 H  [From the Book of Hunting and Carcasses to the Book of swearing] ModelMr. Abdullah Ahmed Al-Zubaidi5. Preservation of blessings and their disappearance in The Holy QuranDr. Larbi Ben Mohamed Lakhnig
Keywords: Journal of Islamic Sciences